2020
DOI: 10.3389/fneur.2020.549038
|View full text |Cite
|
Sign up to set email alerts
|

Giving Researchers a Headache – Sex and Gender Differences in Migraine

Abstract: Migraine is a common neurovascular disorder affecting ∼15% of the general population. Ranking second in the list of years lived with disability (YLD), people living with migraine are greatly impacted by this especially burdensome primary headache disorder. In ∼30% of individuals with migraine, transient neurological symptoms occur (migraine aura) that further increase migraine burden. However, migraine burden is differential with respect to sex. Though one-year prevalences in childhood are similar, starting wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 122 publications
(205 reference statements)
9
52
1
Order By: Relevance
“…Control (n=21) MM (n=9) (MIDAS) and the frequency of pain attacks. 9 Thus, the elevated level of the luteal testosterone in our young MM patients might be a protective physiological mechanism and explain the progression of the disease and the increase in the pain frequency and intensity in older females who demonstrated a decrease in testosterone level, as reported by Li et al 9,15 Progesterone levels were not different in any of the studied groups during follicular as well as luteal phases of the menstrual cycle.…”
Section: Characteristicssupporting
confidence: 60%
“…Control (n=21) MM (n=9) (MIDAS) and the frequency of pain attacks. 9 Thus, the elevated level of the luteal testosterone in our young MM patients might be a protective physiological mechanism and explain the progression of the disease and the increase in the pain frequency and intensity in older females who demonstrated a decrease in testosterone level, as reported by Li et al 9,15 Progesterone levels were not different in any of the studied groups during follicular as well as luteal phases of the menstrual cycle.…”
Section: Characteristicssupporting
confidence: 60%
“…In view that migraine is a more prevalent disorder in women than in men ( 1 ), it can be suggested that these adipokines could be involved in sexual dimorphism in migraine. On the other hand, considering the importance of sex hormones, including estrogen and testosterone, in migraine pathophysiology ( 152 ) and the role of adipose tissue which serves as an endocrine organ by secreting sex hormones ( 153 ), the association between migraine and obesity might be (partly) attributable to sex hormones. Indeed, the relationship between migraine and obesity has been suggested to be the strongest in women of reproductive age ( 106 , 121 ).…”
Section: Association Of Migraine and Obesitymentioning
confidence: 99%
“…Discussion Prior to this study, no researchers used the age-period-cohort model to explore the secular trends of migraine incidence in China from 1990 and 2019. The burden of migraine is differential with respect to sex and is more common in females than in males [18]. Our study indicated that the evaluation rate of migraine incidence in China is higher in females than in males.…”
Section: Age-period-cohort Analysismentioning
confidence: 60%